Fetal outcomes after intentional ingestion of paraquat: A case report - Chen, Jianshi (Medicine (Baltimore), 2020)
RATIONALE: Despite the fact that treatment of paraquat poisoning in pregnant women and their fetuses is challenging and raises ethical issues, it is rarely reported in the literature. We report the case of a pregnant woman who took paraquat intentionally. PATIENT CONCERNS: A 36-year-old woman at 38(+) weeks gestational age, in an apparent suicide attempt, drank 1 mouthful (about 20 ml) of paraquat solution. Ten hours later, her urine dithionate test showed light blue color with a plasma paraquat concentration of 0.547 μg/ml. Six hours after admission, a male infant, whose plasma paraquat concentration was 0.761 μg/ml, together with 0.673 μg/ml in the amniotic fluid measured by high-performance liquid chromatography, was delivered but the woman's lung, liver, and kidney function declined rapidly. DIAGNOSIS: 1. Acute paraquat poisoning; 2. Third trimester of pregnancy (38(+) weeks); 3. Placenta previa. INTERVENTIONS: Because of placenta previa and multiple organ failure, emergency cesarean section, and panhysterectomy were performed for the pregnant woman. Intravenous injection of antibiotic to prevent infection and dexamethasone 30 mg once a day were administered. Mechanical ventilation was performed for the infant and meropenem and penicillin injection was administered. OUTCOMES: The infant died 33 hours after birth while the mother died on the 3rd day after ingestion. LESSONS: Paraquat can enter the fetus through the placenta and the amniotic fluid via fluid exchange. The pathological changes of fetal organs may relate to gestational age, and the prognosis was very poor in both the mother and the fetus.